Tracheal deviation with phrenic nerve palsy after brachial plexus block. Issue 1 (10th March 2021) - Querney, J.; Singh, S. I.; Sebbag, I.
Summary: We present a case of a woman who received a left single‐injection supraclavicular brachial plexus block for analgesia to facilitate upper extremity orthopaedic surgery. Before tracheal extubation she desaturated, was noted to have a low tidal volume and reduced left‐sided air entry on auscultation of the chest. A chest x‐ray taken 1 h following tracheal extubation revealed elevation of the left hemidiaphragm and a rightward shift of the trachea and mediastinal structures, with no evidence of pneumothorax. Findings were in‐keeping with phrenic nerve palsy complicating the brachial plexus block performed. The patient was asymptomatic and discharged home the next day following repeat chest x‐rays. We believe this is the first report of tracheal deviation contralateral to the side of an elevated hemidiaphragm secondary to phrenic nerve palsy from a brachial plexus block.